2024
DOI: 10.1021/acs.langmuir.3c03696
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interfaces in Self-Healable Polymers

Jiahui Liu,
Marek W. Urban

Abstract: It is well-established that interfaces play critical roles in biological and synthetic processes. Aside from significant practical applications, the most accessible and measurable quantity is interfacial tension, which represents a measure of the energy required to create or rejoin two surfaces. Owing to the fact that interfacial processes are critical in polymeric materials, this review outlines recent advances in dynamic interfacial processes involving physics and chemistry targeting self-healing. Entropic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 135 publications
(256 reference statements)
0
3
0
Order By: Relevance
“…Initially, these bonds rupture upon encountering damage (e.g., cracks or microcracks) but then spontaneously reform during the healing process or are triggered by external stimuli such as heat, light, or chemicals . During the initial repair cycles, the polymer’s original structure may be disrupted. As dynamic bonds break and reform, they may not be perfectly rearranged or distributed as in their pristine state, potentially resulting in a decrease in the material’s overall stress resistance. The newly formed bonds may be fewer or weaker compared with their original condition, leading to a reduced effective load-bearing capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, these bonds rupture upon encountering damage (e.g., cracks or microcracks) but then spontaneously reform during the healing process or are triggered by external stimuli such as heat, light, or chemicals . During the initial repair cycles, the polymer’s original structure may be disrupted. As dynamic bonds break and reform, they may not be perfectly rearranged or distributed as in their pristine state, potentially resulting in a decrease in the material’s overall stress resistance. The newly formed bonds may be fewer or weaker compared with their original condition, leading to a reduced effective load-bearing capacity.…”
Section: Resultsmentioning
confidence: 99%
“…While self-healing kinetics, not efficiency, are influenced by the formation of cation–anion pair channels, the main contributing factors to self-healing are monomer molar ratios. Although several studies identified applications or PILs ranging from membrane , or battery , technologies to 3D printed devices, , understanding the interplay of vdW and ionic interactions may lead to new energy harvesting and storage devices, development of devices capable of communications between synthetic and biological interfaces, , or autonomously stimuli-responsive materials.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the intrinsic self-healing materials can achieve the self-healing process with an infinite lifetime using the high efficiencies of reversible chemical reactions. For instance, the generated cracks can be efficiently self-healed via mediating the temperature of the reversible Diels–Alder (D–A) reactions between dienes of furan and monoenes of bismaleimide (BMI) in D–A-type intrinsic self-healing materials (DISMs). In addition, the absence of a heterogeneous catalyst and healing agent also significantly improves the stable abilities and service lives of DISMs . Although the combination of furan and BMI has proven to be highly successful in DISMs, there are still some trade-offs among the self-healing efficiency, tensile strength, and strain.…”
Section: Introductionmentioning
confidence: 99%